Interview to doctor Hugo Caballero Cornejo, teacher of generations, researcher, the reference to national and international level in forensic dentistry “specialty of the millennium” - Suárez Ponce, Daniel Guillermo (2018)
In the interview with the professor Hugo Caballero Cornejo, we will learn about his beginnings, his achievements, his academic, scientific and research contribution to forensic dentistry, being a professional of recognized prestige at a national and international level. We talked about the past, the present and the future of the profession in the specialty that is developed through its various thematic areas, such as professional responsibility and human identification, establishing that the specialty of “forensic dentistry is the specialty of the millennium” for being the rector of all the specialties of the profession, for legal and ethical implications that the dentist must obey in professional practice. The notorious teacher is the author and editor of the book “Legal and Forensic Dentistry”.